PROGRAM PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL (KAT DI DESA SUNGAI TOHOR BARAT KECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI - Yulinawati "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research intent to know Community empowerment program devastated Custom (KAT) at Tohor's River Village district West East Tall Bank Regency archipelagic Meranti. Empowerment program constitute federal policy that plays ball with local government to be able to increase citizen life quality devastated Custom Community (KAT) to aim the better so most composes independent citizen it, participative and useful. In focus this research which is to see how Community empowerment program devastated Custom (KAT) can happening and how its implement. Method that is utilized in this research is deskripftif kualitatif, collecting is data by interview, observation, and documentation. Researcher utilizes research informan via to y. person by use of purposive is sampling , which is sample determination tech with consideration particular. Result observationaling to point out Community Empowerment Program devastated Custom (KAT) at Tohor's River Village district West East Tall Bank Regency archipelagic Meranti stills reducing the coordination among local government with apparatus silvan and local government with devastated Custom Community citizen (KAT) that own, so Community empowerment program devastated Custom (KAT) at Tohor's River Village West was optimal.Kata kunci: Pemberdayaan, Komunitas Adat Terpencil (KAT)